Pendekatan Naratif Dokumenter ”Pengamen Digital” Sebagai Bentuk Transformasi Seni Musik Jalanan - Dimas Yoki Alfianto; Sangga Arta Witama; Muhammad Iqbal Naufal (Universitas Budi Luhur, 2026)
The documentary film Pengamen Digital explores the transformation of street music in the digital era, as street performers begin to utilize platforms like TikTok to reach wider audiences and create virtual performance spaces. This shift not only opens new economic opportunities but also reshapes public perception where street performers were once seen as part of a traditional art form, they are now increasingly viewed as participants in a modern artistic ecosystem. However, these performers still face significant challenges, including social stigma, limited access to public spaces, and frequent conflicts with authorities. Through the stories of the performers, their supporters, and their families, this documentary highlights the social impacts of digitalization and the importance of innovation in preserving cultural expression. Pengamen Digital also serves as a form of social advocacy, encouraging more inclusive dialogue among artists, the public, and the government to help build a fairer and more sustainable art ecosystem.